A56: Macrophage Activation Syndrome in Patients With Systemic Juvenile Idiopathic Arthritis Treated With Tocilizumab. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Ravelli, Angelo; Schneider, Rayfel; Weitzman, Sheila; Devlin, Clare; Daimaru, Kaori; Yokota, Shumpei; Takei, Syuji; De Benedetti, Fabrizio
Abstract : Background/Purpose: Macrophage activation syndrome (MAS) is a severe, potentially fatal complication of systemic juvenile idiopathic arthritis (sJIA).1 Changes in therapies, including biologics, 2 3 may trigger MAS. Interleukin‐6 (IL‐6) plays a major pathogenic role in sJIA; data in animals suggest that high IL‐6 levels contribute to the triggering of MAS.4 Treatment with the IL‐6 receptor inhibitor tocilizumab (TCZ) is very effective in patients with sJIA.2 In this study, we investigated the rates and features of MAS occurring during TCZ treatment in patients with sJIA. Methods: Data were collected from patients with sJIA treated with TCZ in the international phase 3 trial (TENDER), 4 clinical trials in Japan, and the Japanese postmarketing surveillance (JPMS) program. Reported MAS events or disease flares associated with alanine aminotransferase/aspartate aminotransferase (ALT/AST) elevations were collected. Worksheets with event information were assessed by an independent panel (2 pediatric rheumatologists, 1 pediatric hematologist with MAS expertise) overseen by the TENDER lead investigator. Cases were adjudicated as definite MAS, potential MAS, not MAS, or insufficient data. Results: The data set included 112 patients from TENDER (403.0 patient‐years' [PY] exposure to TCZ), 149 patients from the Japanese trials (326 PY), and 366 patients from the JPMS program (523.9 PY). Of 31 cases reviewed, 22 events were adjudicated as definite or potential MAS: 5 from TENDER (3 definite, 2 potential), 6 from the Japanese trials (3 definite, 3 potential), and 11 from the JPMS program (5 definite, 6 potential). The rates/100 PY of definite/potential MAS were 1.24 (95% CI, 0.4–2.90) in TENDER, 1.84 (95% CI, 0.68–4.00) in the Japanese trials, and 2.10 (95% CI, 1.05–3.76) in the JPMS program. Features contributing to the adjudication of definite MAS are listed in the1 . All 11 events adjudicated as definite MAS met the preliminary MAS diagnostic guidelines.6 All definite and potential MAS resolved with the exception of MAS in a patient from the Japanese phase 3 study who died after respiratory/cardiac arrest. Conclusion: The use of TCZ does not appear to be associated with increased risk for MAS in sJIA. There were no unusual clinical or laboratory features in these MAS cases.